Propuesta integral para la reducción de pérdidas en el sistema de acueducto de la empresa Red Vital ESP, del municipio de Paipa (2023)
In the following work, it is described the process of water- supply system conducted by RED VITAL E, S, P company in order to purify water. In this water catchment process, treatment, distribution and marketing, some technical and commercial water losses are identified by different concerns. This project aims at working on the causes of technical and commercial losses of unaccounted water, due to no actions to reduce the losses have been carried out, except the arrangements done previously by the company.